(untitled) (Collection of scientific works «Modern structures of metal and wood», 2025)
Modern methods for determining the initial modulus of elasticity of solid wood are analyzed. The article presents the results of experimental and theoretical research on the selection of values of the initial modulus of elasticity of solid wood for determining the theoretical bearing capacity of bending unreinforced and reinforced elements made of glued laminated timber. The purpose of the work is to determine the features of determining the modulus of elasticity of wood and the reliability of determining the theoretical bearing capacity of bending elements made of wood using the deformation method. It is established that the closest results are the results of calculating the theoretical bearing capacity of bending elements made of glued laminated timber to the experimental ones using a deformation model, which uses the initial modulus of elasticity established on the basis of solid wood from which the structure is made. The deformation model for calculating bending elements made of glued laminated timber involves the use of determined normal stresses based on deformations that have arisen in the normal cross-section of the bending element under external loading. The stresses in the calculated normal cross-section are described by different functions in three different sections of the cross-section height. The first section is the tension section, starting from the bottom of the element to the neutral line and described by a linear function; the second section is the compression section, from the neutral line to the maximum value of the compressive stresses is described by a nonlinear function; the third section is also a compression section, from the end of second section to the top of the bending element is described by a nonlinear function taking into account the appearance of a fold.